Rotational gait problems in the presence of femoral deformity - Musagara, Arik Rehani; Salami, Firooz; Putz, Cornelia; Beckmann, Nicholas A.; Götze, Marco; Wolf, Sebastian Immanuel (Bioengineering, 2025)
The relationship between femoral deformity and gait deviation is complex. Femoral anteversion can be assessed using the trochanter prominence angle test or by imaging techniques. Hip rotation during gait can be determined using conventional 3D gait analysis methods including palpation of femoral epicondyles or by using functional calibration. This study re-evaluates the indications for femoral osteotomies in this context. Hip rotation was analysed using predictive and functional methods in 80 patients who were referred for gait analysis due to rotational gait issues. Femoral anteversion was determined both manually and via MRI. In severe cases of femoral malalignment, the trochanter prominence angle test systematically underestimates the deformity by up to 15° compared to MRI results. Hip rotation, as measured by functional methods, also underestimates the outcome obtained by conventional methods, by up to 5°. Regardless of the method used, significant variability in hip rotation is observed during gait when the femoral deformation is moderate (anteversion between 0° and 30°). More severe deformities are not fully compensated for during gait. In cases of severe femoral malalignment, the functional change after osteotomy does not match the amount of derotation. Furthermore, both the trochanter prominence angle test and hip rotation during gait, as monitored via functional methods, underestimate the problem in the transverse plane.